Design de serviços públicos à luz da centralidade do usuário na intermediação de mão de obra no SINE-PBH - Oliveira, Manoel Messias Tolentino de (2021)
This dissertation applies the principles, tools and prescriptions of Service Design, aiming to answer how this approach can contribute to the analysis and proposition of public services centered on the citizen. Qualitative research was carried out in the labor intermediation serviceof the Sistema Nacional de Emprego (SINE) and offered by the BH Resolve agency, which is part of the organizational structure of the Municipality of Belo Horizonte. The research included interviews with managers and agency attendants, open questionnaires applied to members of the Conselho Municipal do Trabalho, Emprego e Renda de Belo Horizonte (CMTER) and direct observation. From the data analysis, artifacts related to the user journey and the service ecosystem were elaborated, in addition to indicators to measure the centrality of the citizen. The results of the study revealed misalignments between what is offered and the realities and needs of the public and, with the findings of the study, improvements were suggested for greater convergence of the service to its users. Given this, Service Design proved to be a promising way to design and realign citizen-centric public services.